2021
DOI: 10.1016/j.ultrasmedbio.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Lymphatic and Intravenous Contrast-Enhanced Ultrasound for Evaluation of Cervical Lymph Node Metastasis from Papillary Thyroid Carcinoma: A Preliminary Study

Abstract: The aim of this prospective study was to evaluate the value of the combination of lymphatic contrastenhanced ultrasound (LCEUS) and intravenous contrast-enhanced ultrasound (IVCEUS) for the identification of cervical lymph node metastasis (CLNM) from papillary thyroid carcinoma (PTC). From November 2018 to March 2019, 24 consecutive patients with PTC were evaluated. All patients underwent routine US, LCEUS and IVCEUS. Pathology was used as the gold standard. After injection of a contrast agent into the thyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 24 publications
4
38
3
Order By: Relevance
“…20 1.20 ml in four studies, 9,13,22,23 1 ml in one study, 21 and 0.40 ml in one study. 24 The scan time after injecting contrast agent was 180 s or more in one study, 21 120 s or more and less than 180 s in four studies, 9,20,22,23 90 s in one study, 13 and 30 s in one study. 24 All of the studies reported saline was used after contrast agent injection, except one study that did not describe the dose of saline used, 24 the other six articles all used 5 ml of saline.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 89%
See 4 more Smart Citations
“…20 1.20 ml in four studies, 9,13,22,23 1 ml in one study, 21 and 0.40 ml in one study. 24 The scan time after injecting contrast agent was 180 s or more in one study, 21 120 s or more and less than 180 s in four studies, 9,20,22,23 90 s in one study, 13 and 30 s in one study. 24 All of the studies reported saline was used after contrast agent injection, except one study that did not describe the dose of saline used, 24 the other six articles all used 5 ml of saline.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 89%
“…Seven articles were included with 1049 patients and 894 lymph nodes. 9,13,[20][21][22][23][24] The number of lymph nodes varied from 48 to 319 in a single study. The mean patient ages of the included studies varied from 35.00 ± 6.20 to 52.60 ± 13.50.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations